Obstructed Hemivagina, Uterine Didelphys, and Ipsilateral Renal Agenesis: A Case Report of OHVIRA Syndrome - Güneş, Mehtap; Taşar, Sevinç; Karaman Ayyıldız, Hayriye Nihan; Kale, İbrahim and Alp Uydu, Funda and Muhcu, Murat (Acta medica Lituanica, 2025)
Background: Obstructed hemivagina and ipsilateral renal agenesis (OHVIRA) syndrome is a rare congenital anomaly of the female urogenital tract. This report presents the clinical features, diagnostic approach, and management of an adolescent girl with OHVIRA syndrome. Clinical case: A 14-year-old female was admitted with abdominal pain and irregular menstruation. Ultrasonography and MRI demonstrated uterus didelphys with right-sided hematometrocolpos and ipsilateral renal agenesis. External genital examination revealed an intact hymen with a bluish bulge 2 cm above the hymenal ring. Surgical exploration confirmed an obstructed right hemivagina, which was opened while preserving hymenal integrity. Menstrual blood was drained, and a Foley catheter was placed temporarily to ensure patency. The postoperative course was uneventful, and the patient was discharged on the second day. Discussion and Conclusions: This case illustrates successful surgical management of OHVIRA syndrome while preserving hymenal integrity. Early diagnosis and imaging are essential to prevent complications such as hematometrocolpos, endometriosis, and infertility.